003 Adult-onset cerebellar ataxia due to mutations in the CABC1/ADCK3 gene. Issue 3 (9th February 2012) - Horvath, P O; Czermin, B; Gulati, S; Pyle, A; Hassani, A; Foley, C; Taylor, R W; Chinnery, P F
Abstract : Inherited ataxias are heterogeneous disorders affecting both children and adults. The primary cause can be identified in about half of the children and the hit rate is even lower in adults. In 22 patients with unexplained recessive or sporadic ataxia sequencing of known coenzyme Q10 (CoQ10) deficiency genes detected CABC1/ADCK3 mutations in six patients (four families), who presented with cerebellar ataxa, epilepsy, spasticity and muscle symptoms. Two patients had a later onset (15 and 27 years) with mild disease. It is extremely important to screen for CABC1/ADCK3 mutations in ataxia, because is potentially treatable and it can present in adult life.